Lateral variation in crustal and mantle structure in Bay of Bengal based on surface wave data. (January 2018) - Kumar, Amit; Mukhopadhyay, Sagarika; Kumar, Naresh; Baidya, P.R.
Abstract: Surface waves generated by earthquakes that occurred near Sumatra, Andaman-Nicobar Island chain and Sunda arc are used to estimate crustal and upper mantle S wave velocity structure of Bay of Bengal. Records of these seismic events at various stations located along the eastern coast of India and a few stations in the north eastern part of India are selected for such analysis. These stations lie within regional distance of the selected earthquakes. The selected events are shallow focused with magnitude greater than 5.5. Data of 65, 37, 36, 53 and 36 events recorded at Shillong, Bokaro, Visakhapatnam, Chennai and Trivandrum stations respectively are used for this purpose. The ray paths from the earthquake source to the recording stations cover different parts of the Bay of Bengal. Multiple Filtering Technique (MFT) is applied to compute the group velocities of surface waves from the available data. The dispersion curves thus obtained for this data set are within the period range of 15–120 s. Joint inversion of Rayleigh and Love wave group velocity is carried out to obtain the subsurface information in terms of variation of S wave velocity with depth. The estimated S wave velocity at a given depth and layer thickness can be considered to be an average value for the entire path covered by the corresponding ray paths. However, we observe variation in the value of S wave velocity and layer thickness from data recorded at different stations, indicating lateral variation in these two parameters. Thick deposition of sediments is observed along the paths followed by surface waves to Shillong and Bokaro stations. Sediment thickness keeps on decreasing as the surface wave paths move further south. Based on velocity variation the sedimentary layer is further divided in to three parts; on top lay unconsolidated sediment, underlain by consolidated sediment. Below this lies a layer which we consider as meta-sediments. The thickness and velocity of these layers decrease from north to south. The crustal material has higher velocity at the southern part compared to that at the northern part of Bay of Bengal indicating that it changes from more oceanic type in the southern part of the Bay to more continental type to its north. Both Moho and lithosphere − asthenosphere boundary (LAB) dips gently towards north. Thicknesses of both lithosphere and asthenosphere also increase in the same direction. The mantle structure shows complex variation from south to north indicating possible effect of repeated changes in type of tectonic activity in the Bay of Bengal.